Drosophila females receive male substrate-borne signals through specific leg neurons during courtship. - McKelvey, E.G.Z.; Gyles, J.P.; Michie, K.; Barquín Pancorbo, V.; Sober, L.; Kruszewski, L.E.; Chan, A.; Fabre, C.C.G. (Current Biology, 2021)
Substrate-borne vibratory signals are thought to be one of the most ancient and taxonomically widespread communication signals among animal species, including Drosophila flies.1-9 During courtship, the male Drosophila abdomen tremulates (as defined in Busnel et al.10) to generate vibrations in the courting substrate.8,9 These vibrations coincide with nearby females becoming immobile, a behavior that facilitates mounting and copulation.8,11-13 It was unknown how the Drosophila female detects these substrate-borne vibratory signals. Here, we confirm that the immobility response of the female to the tremulations is not dependent on any air-borne cue. We show that substrate-borne communication is used by wild Drosophila and that the vibrations propagate through those natural substrates (e.g., fruits) where flies feed and court. We examine transmission of the signals through a variety of substrates and describe how each of these substrates modifies the vibratory signal during propagation and affects the female response. Moreover, we identify the main sensory structures and neurons that receive the vibrations in the female legs, as well as the mechanically gated ion channels Nanchung and Piezo (but not Trp?) that mediate sensitivity to the vibrations. Together, our results show that Drosophila flies, like many other arthropods, use substrate-borne communication as a natural means of communication, strengthening the idea that this mode of signal transfer is heavily used and reliable in the wild.3,4,7 Our findings also reveal the cellular and molecular mechanisms underlying the vibration-sensing modality necessary for this communication.